Caipora and the conservation of natural resources in tropical forests in the South Recôncavo region, Bahia State, Northeast Brazil - Pereira Aguiar, Leonardo Matheus; Costa Neto, Eraldo Medeiros; Santos Fita, Dídac (Ethnobiology and Conservation, 2023)
This study aimed to investigate the relationship between the imaginary of Caipora and environmental conservation in Serra da Jiboia. Data obtained through the application of semi-structured interviews and Likert scale. All data were analyzed qualitatively and quantitatively. Through factor analysis, it was possible to identify four factors that explain the variations in responses given by residents of the region, suggesting a strong belief in the spiritual entities of the forest and its importance for nature conservation. 57 interviews were carried out and the socioeconomic characterization of the participants was carried out, were composed of men and women predominantly between 50 years or more and who carry out agricultural activities. Although Catholicism is the predominant religion in the region, belief in Caipora was high, being related to the appreciation and preservation of local nature. Through the chi-square test, it was possible to verify a statistically significant relationship between the belief in Caipora and the activities carried out in the forest by the interviewees. This study contributes to the understanding of the relationship between popular beliefs and environmental conservation, highlighting the importance of considering local knowledge for the development of public policies aimed at nature preservation.